AI BASED FACIAL RECOGNITION TECHNOLOGY AND CRIMINAL JUSTICE: ISSUES AND CHALLENGES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Law enforcement agencies in many countries have initiated the use of AFRS (Automated FacialRecognition System),it’s an artificial intelligence system that compares face traits automatically,to identify unknown suspects using images and other social media platforms. Its capabilities arefast developing in conjunction with artificial intelligence, and it has a lot of potential for solvingcrimes. However, it also has a negative connotation. There are substantial privacy and ethicalconsiderations that necessitate legislation and regulation. The Ministry of Home Affairs of Indiahas released a new plan for AFRS aimed at upgrading law-enforcement agencies for the purposeof detection of criminals, proper data exchange among law enforcement agencies throughout theglobe. It is indeed evident to say, India is third largest country in technological development andthe citizens are coping up with these changes. The author proposes to examine the emergence ofAutomated Facial Recognition System, contemporary uses, and legislative developments invarious countries like US, UK and Australia, as well as doing an ethical examination of theconcerns that may arise during its implementation. The author will also implicate the authenticityof FIR registered against unknown person through the use of AFRS, and legislations related to it.Ethical considerations are used to mediate conflicting issues with reference to modern innovationvis-à-vis public safety mechanism, privacy and democratic responsibility.